Does it fit? The relationships between personality, decision autonomy fit, work engagement, and emotional exhaustion in self-managing organizations - Maria Doblinger; Janina Class (International Journal of Selection and Assessment, 2023)
The novel organizational form of self-managing organizations decentralizes decision authority, thus promising higher adaptability and sustainability. However, recent practical experiences showed that such organizations struggle with employee turnover and lack of engagement, and thus, levers to improve personnel selection are required. This work investigated the relationship between person-environment fit regarding perceived and ideal decision autonomy and the employee outcomes of work engagement and emotional exhaustion in self-managing organizations. Furthermore, the associations with personality traits were examined. The study relied on cross-sectional survey data from two subsamples of employees working in self-managing and traditional organizations. Group comparison was used to test the elevated level of decision autonomy in self-managing organizations, polynomial regression with response surface analysis was used to investigate the effect of (mis-)fit, and multiple regression analyses evaluated the relationship with personality traits. The findings showed that employees in self-managing organizations experienced higher decision autonomy than those in traditional organizations. Additionally, the fit between ideal and perceived decision autonomy predicted higher work engagement, while extraversion, openness to experience, and low neuroticism predicted higher ideal decision autonomy. As a result, individual person-environment fit regarding decision autonomy and personality requires attention in self-managing organizations to engage employees. The findings imply that the effect of decision autonomy on engagement is not positive per se but depends on the intraindividual characteristics, which must be of concern when decentralizing decision authority organization-wide. Therefore, personnel selection and recruitment processes in self-managing organizations should consider ideal decision autonomy and personality traits as assessment criteria.
Keywords: 650; decision autonomy; ideal decision autonomy; personality; person-environment fit; self-managing organization